Cold Damage on Palms - Timothy K. Broschat (EDIS)
Revised! ENH-92, a 6-page illustrated fact sheet by Timothy K. Broschat, describes how cold temperatures affect palms and how to treat them following a cold weather event. Includes references. Published by the UF Department of Environmental Horticulture, September 2010.